Dual roles of CD11b+CD33+HLA-DR-/lowCD14- myeloid-derived suppressor cells with a granulocytic morphology following allogeneic hematopoietic stem cell transplantation: from inflammation promoters to immune suppressors within 90 days - Ni, Ming; Cui, Jing; Yang, Xin; Ding, Yuntian; Zhao, Peng; Hu, Tianzhen; Zhan, Yun; Kang, Qian; Hu, Xiuying; Zhao, Jiangyuan; Xu, Yao; Chen, Lu; et al. (Frontiers in Immunology, 2024)
Granulocytic myeloid-derived suppressor cells (G-MDSCs) show fast recovery following allogeneic hematopoietic stem cell transplantation (allo-HSCT) constituting the major part of peripheral blood in the early phase. Although G-MDSCs mediate immune suppression through multiple mechanisms, they may also promote inflammation under specific conditions. In this study, we investigated the role of G-MDSCs on post-transplantation immunity. G-MDSCs were collected from 82 patients after allo-HSCT within 90 days. The results showed that G-MDSCs promoted inflammation in the early-stage, by facilitating cytokine secretion and proliferation of T cells, as well as their differentiation into proinflammatory T helper subsets. At day 28, patients with a higher number of G-MDSCs exhibited an increased risk of developing grades II-IV aGvHD. Besides, adoptive transfer of G-MDSCs from patients at day 28 into humanized mice exacerbated aGvHD. However, at day 90, G-MDSCs led to immunosuppression, characterized by upregulated expression of indoleamine 2,3-dioxygenase gene and interleukin-10 secretion, coupled with the inhibition of T cell proliferation. Furthermore, transcriptional analysis of G-MDSCs at day 28 and day 90 revealed that 1445 genes were differentially expressed. These genes were associated with various pathways, revealing the molecular signatures of early post-transplant differentiation in G-MDSCs. In addition, genes linked to the endoplasmic reticulum stress were upregulated in patients without aGvHD. The acquisition of immunosuppressive function by G-MDSCs may depend on the activation of CXCL2 and DERL1 genes. In conclusion, our findings revealed the alteration in the immune characteristics of G-MDSCs within the first 90 days post-allo-HSCT. Moreover, the quantity of G-MDSCs at day 28 may serve as a predictive indicator for the development of aGvHD.